Refeeding Syndrome: A Multidisciplinary Challenge in Patient Care – A Narrative Review - Kazi, Fauzia Jawaid; Devi, Rajita (International Journal of Medical Research and Review, 2024)
Refeeding syndrome (RFS) is a serious metabolic condition that occurs when nutrition is reintroduced to malnourished individuals after prolonged fasting or starvation. The abrupt shift from catabolism to anabolism triggers rapid insulin release, leading to critical electrolyte imbalances such as hypophosphatemia, hypokalaemia, and hypomagnesemia, which can result in cardiac, respiratory, and neurological complications. The incidence of RFS varies across populations, with higher prevalence in ICU patients, those receiving total parenteral nutrition, the elderly, individuals with chronic illnesses, pregnant women, and those with anorexia nervosa. Major risk factors include prolonged fasting, malnutrition, gastrointestinal diseases, and alcoholism. Clinical features range from fluid retention, arrhythmias, confusion, and muscle weakness to life-threatening outcomes like heart failure or respiratory collapse. Prevention involves gradual reintroduction of calories, electrolyte monitoring, and thiamine supplementation to minimize complications. Nurses play a pivotal role by identifying at-risk patients, monitoring electrolyte levels, and ensuring appropriate nutritional support. Their responsibilities extend to educating patients and families, providing emotional support, and coordinating care with dietitians and physicians to prevent adverse outcomes. A multidisciplinary approach is essential for the safe management of RFS, ensuring better patient recovery and survival.